Inovasi Pengolahan dan Pengemasan Ikan Bulu Ayam Berbasis Nilai Gizi untuk Penguatan Industri Rumah Tangga - Cucun Setya Ferdina; Kristian Triatmaja Raharja; Nindi Pramesthi Vardila Putri; Nuraini Fauziah; Honesty Pujiyani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The fish processing and packaging program based on nutritional value aims to enhance the quality and competitiveness of processed products produced by IRT Jiddah and IRT Barokah in Surabaya. This initiative is driven by the partners' reliance on traditional processing methods, which are inefficient and can reduce product quality. The implementation method consists of five main stages: Focus Group Discussion (FGD) to identify issues, training in fish processing into nutritious products such as nuggets, sausages, fish balls, and salted fish from Thryssa mystax, training in packaging using a vacuum sealer, digital marketing training through social media, and production mentoring. The results indicate an improvement in the partners' skills in processing, packaging, and marketing, supported by modern technology such as food dehydrators and vacuum sealers. This program successfully enhanced product quality, shelf life, market value potential, and expanded market reach. However, participants' initial limited knowledge of modern technology and digital marketing remains challenging. The program's sustainability is expected to be improved through introductory technology sessions and discussion forums to encourage continuous application of the acquired skills.